An investigation of in-situ AFP process parameters using CF/LM-PAEK. (7th October 2020) - Schiel, Ines; Raps, Lukas; Chadwick, Ashley R.; Schmidt, Isabelle; Simone, Manuel; Nowotny, Sebastian
Abstract: In recent years the use of thermoplastics has become popular in aerospace applications, with a primary focus on fiber-reinforced composites. Displaying greatly improved mechanical properties, new components using these materials still need to be characterized and their suitability for aviation applications demonstrated. A common restriction to the implementation of fiber-reinforced thermoplastic parts is the almost default autoclave manufacturing, which is both time consuming and expensive. Aiming for a more economical final product, this study utilizes a one-step in-situ Automated Fiber Placement (AFP) process to produce samples for mechanical and thermal characterization. The recently developed and highly popular material CF/LM-PAEK was used within this study, with the four major AFP processing parameters varied to assess material sensitivity. Test samples were manufactured using Design of Experiment (DoE). Subsequently, single lap shear (SLS) and differential scanning calorimetry (DSC) tests were performed to assess consolidation quality. With rising tooling temperature, both SLS strength and crystallinity increase up to 31 MPa and 25%, respectively. A post-manufacturing tempering process improved crystallinity of the tested CF/LM-PAEK specimens up to 29% and SLS strength up to 38 MPa. Within the tested parameter range, CF/LM-PAEK appeared to be unaffected by increasing layup speed, which is a promising aspect with regard to faster industrial production. Graphical Abstract: